Let, $$E\subset \mathbb R$$ be a non empty bounded above set. Define $$ -E = \{ -x : x \in E \}.$$ Then, $\operatorname{inf} (-E) = -\operatorname{sup}(E)$.

Proof - It follows from the completeness property that $$\exists x_o < x , \forall x_o \in E$$

such that, $$ \operatorname{sup}(E) = x \tag {1} \label{1}$$

Since, it is already given that the set is bounded, it must have a lower bound. $$ \exists x_o < x, \forall x_o \in E,$$ we have shown already.

Now, $$ \forall x_o>x ,\exists x_o \notin E$$

such that, $$ \operatorname{inf}(E) = -x \tag {2} \label{2}$$

From (1) and (2), we get -

$$\operatorname{inf}(E) = -x = -\operatorname{sup}(E)$$

Hence, proved. (black dot to the far left)

I know there might be many logic blunders. I hope to solidify my logic and understanding through the feedback! :D

  • $\begingroup$ 1) ∃xo<x∀xo∈E this notation is wrong. You mean $\exists x; \forall x_o\in E x_o < x$. But this a only notation. $\endgroup$ – fleablood Dec 5 '16 at 0:50
  • 1
    $\begingroup$ 2)"Since, it is already given that the set is bounded, it must have a lower bound. " It was not given that the set was bounded. It was only given that the set was bounded above. $\endgroup$ – fleablood Dec 5 '16 at 0:51
  • $\begingroup$ 3) "Since, it is already given that the set is bounded, it must have a lower bound. ∃xo<x,∀xo∈E," That's an upper bound not a lower bound. $\endgroup$ – fleablood Dec 5 '16 at 0:53
  • $\begingroup$ 4)"Now, ∀xo>x∃xo∉E such that, inf(E)=−x" in english. "Anything larger than the least upper bound is not in E, therefore the greatest lower bound is the negative of the least upper bound".... ???HUH???? I can't even begin to understand why you would conclude that. if E = [1,2] then if x > 2, x isnt in [1,2]. How could this possibly imply $\inf [1,2] = -2$? $\endgroup$ – fleablood Dec 5 '16 at 1:03
  • $\begingroup$ Did you mean -E in some of the places you wrote E. I can't really follow your logical notation. It seems like you might be trying to say "if x0 > x then x0 not in E and therfore if x1 < -x then x1 not in -E and so -x is a lower bound. But you never specifically stated the implication so it is hard to tell if that was what you meant to say. $\endgroup$ – fleablood Dec 5 '16 at 1:09

If you have that $\exists x_{0}$ such that $\forall x\in E$, $x\le x_{0}=sup(E)$ if you multiply by $-1$ the inequality you have that $y=-x\ge -x_{0}=-sup(E)$, $\forall x\in E$, $\forall y\in -E$, you have that $inf(-E)\ge -sup(E)$. So you have to prove that they are equals. (Hint: prove the other inequality).

  • $\begingroup$ I think you're misinterpreting what the OP means - when they write "$\exists x_0<x$," I believe they mean "$\exists x>x_0$." $\endgroup$ – Noah Schweber Dec 5 '16 at 0:46
  • $\begingroup$ Yes, I think I understand that, but I change the notation for a better understanding. $\endgroup$ – Skullgreymon Dec 5 '16 at 0:50

You seem to be using $x$ as both the supremum and infimum of $E$. You can't do this, and indeed you can't even assume $E$ is bounded below; all you know is that $E$ is bounded above! Also, your conclusion doesn't involve $-E$ at all, whereas you're supposed to be proving a statement about $-E$ and $E$.

EDIT: In particular, your conclusion that $-x=\inf(E)$ is completely unjustified, and indeed could be false: suppose $E=(1, 2)$. Then $x=2$. Is $\inf(E)=-2$?

Here's a hint: suppose $x=\sup E$. Is $-x$ a lower bound for $-E$? Is it the greatest lower bound?

Also, your quantification is mostly backwards: to write "There is an element bigger than everything in $E$," you write $$\exists x\forall x_0\in E(x>x_0).$$


You need to prove: $\inf (-E) = - \sup E$.

For instance if $E = (-\infty,-5]$ then $-E = [5, \infty)$. $\sup E = -5$. As it so happens, $\inf -E = 5 = -\sup E$. (What are the odds?)


Outline of what you want to do:

Since $E$ is bounded above we know $\sup E$ exists.

The definition of $\sup$ is that:

1) $\sup E \ge x$ for all $x \in E$.

2) If $y < \sup E$, $y$ is not an upper bound. i.e. if $y < \sup E$ than there exists an $x \in E$ so that $y < x$.

Now $a < b \iff -a > -b$ and $x \in E \iff -x \in -E$.

So we can restate statement 1) and 2) using $-x,-y, -\sup E,$ and $-E$ rather instead of $x,y \sup E$ and $E$.

The restatement of 1) and 2) will satisfy the definition of $\inf -E$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.